Expression of CEACAM1 or CEACAM5 in AZ‐521 cells restores the type IV secretion deficiency for translocation of CagA by Helicobacter pylori. (8th November 2018) - Tegtmeyer, Nicole; Harrer, Aileen; Schmitt, Verena; Singer, Bernhard B.; Backert, Steffen
Abstract: Helicobacter pylori represents an important pathogen involved in diseases ranging from gastritis, peptic ulceration, to gastric malignancies. Prominent virulence factors comprise the vacuolating cytotoxin VacA and the cytotoxin‐associated genes pathogenicity island ( cag PAI)‐encoded type IV secretion system (T4SS). The T4SS effector protein CagA can be translocated into AGS and other gastric epithelial cells followed by phosphorylation through c‐Src and c‐Abl tyrosin kinases to hijack signalling networks. The duodenal cell line AZ‐521 has been recently introduced as novel model system to investigate CagA delivery and phosphorylation in a VacA‐dependent fashion. In contrast, we discovered that AZ‐521 cells display a T4SS incompetence phenotype for CagA injection, which represents the first reported gastrointestinal cell line with a remarkable T4SS defect. We proposed that this deficiency may be due to an imbalanced coexpression of T4SS receptor integrin‐β1 or carcinoembryonic antigen‐related cell adhesion molecules (CEACAMs), which were described recently as novel H. pylori receptors. We demonstrate that AZ‐521 cells readily express integrin‐β1, but overexpression of integrin‐β1 constructs did not restore the T4SS defect. We further show that AZ‐521 cells lack the expression of CEACAMs. We demonstrate that genetic introduction of either CEACAM1 or CEACAM5, but not CEACAM6, in AZ‐521 cells is sufficient to permit injection and phosphorylation of CagA by H. pylori to degrees observed in the AGS cell model. Expression of CEACAM1 or CEACAM5 in infected AZ‐521 cells was also accompanied by tyrosine dephosphorylation of the cytoskeletal proteins vinculin and cortactin, a hallmark of H. pylori ‐ infected AGS cells. Our results suggest the existence of an integrin‐β1 ‐ and CEACAM1‐ or CEACAM5‐dependent T4SS delivery pathway for CagA, which is clearly independent of VacA. The presence of two essential host protein receptors during infection with H. pylori represents a unique feature in the bacterial T4SS world. Further detailed investigation of these T4SS functions will help to better understand infection strategies by bacterial pathogens.